IMPLEMENTASI CHAT-GPT DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Setiawati, Lilis; Rofiqa Nasri, Ferriza Nur; Amalia, Ayu Rizki (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The development and use of digital in the learning context has an influence on the ability of Islamic Religious Education (PAI) teachers to carry out learning. In the modern era which is influenced by advances in information technology, the application of AI in the form of Chat-Gpt is becoming increasingly relevant in helping educators in learning. However, the application of AI also faces challenges, such as understanding the complex Islamic religious context and ethical issues related to data privacy and information security. This research aims to determine the implementation of using Chat-Gpt based AI in the implementation of Islamic religious education learning. This research uses a qualitative approach. This type of research approach is a case study. The results of this research show that with the implementation of Chat-Gpt teachers can access how to create learning media, teaching modules and even create questions for the learning evaluation stage. The implications of this research make it easier for teachers to carry out learning activities because they are helped by Artificial Intelligence, namely Chat-Gpt.